Management of Guidance and Counseling Services (BK) - Afrilia Sirani; Santoso, Yulianto (Global Action and Education for Society, 2025)
This research was motivated by the desire to understand how the management of counseling services is conducted at SMK Kartika 1-2 Padang. The purpose of this study is to gather information regarding the planning, organizing, implementation, and supervision of counseling service programs at SMK Kartika 1-2 Padang. The research method used is qualitative with a case study approach, involving data sources such as the principal, counseling teachers, subject teachers, and students. Data collection instruments include observation, interviews, documentation, and recording devices. The data analysis techniques used are data reduction, data presentation, and conclusion drawing. In ensuring data validity, the researcher employed technique triangulation, source triangulation, and time triangulation. Overall, although the management of counseling services at SMK Kartika 1-2 Padang has been running well, there are still challenges that require further attention, particularly in improving facilities and strengthening students' trust in the counseling services. The supporting factors in the management of counseling services at SMK Kartika 1-2 Padang include human resources such as the principal, vice principal, teachers, school staff, and students. Meanwhile, the inhibiting factors are inadequate facilities, lack of collaboration and communication among involved parties, and insufficient supervision of the implemented service programs.